Corporate Capitalism in Contemporary South Asia : - Reed, Ananya Mukherjee (Palgrave McMillan, 2003)
This volume presents a comparative and comprehensive discussion of corporate economies in South Asia today. It approaches the theme from a socio-historical perspective that examines corporate economies in relation to the state, state formation, globalization and economic reforms and the nature of corporate ownership. It also looks at some of South Asia's well-known but inadequately understood institutions such as caste, thus questioning some major tenets of the conventional wisdom that shape our thinking about contemporary Asia.